Technology and vocational education for sustainable development : empowering individuals for the future - Pavlova, Margarita [Verfasser] (Springer Science + Business Media, 2009)
"The ways education for sustainable development can be addressed in teaching and learning are among the most urgent challenges for modern educational theory and practice. This book explores the unique contribution technology and vocational education can provide to meet these urgent needs. Part 1 examines various concepts from different areas of knowledge that are used to develop a comprehensive understanding of the ways sustainable development, education for sustainable development and empowerment are related and can be conceptualised. Practical strategies are suggested and a model for pre-service teacher training programs is developed. Part 2 explores how general issues are reflected in local norms, values and behaviours within the Russian context. The case study illustrates the importance of understanding the political and sociocultural context of a country in order to develop empowerment strategies that work for that particular society as they reflect specific local histories, values and traditions." (Publisher, BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; L 1.3 Curriculumentwicklung; I 2.2.2 Osteuropa; Technische Entwicklung; Neue Technologien; Berufsbildung; Nachhaltige Entwicklung; Curriculumentwicklung; Fallstudie; Russland